Strongly Coupled Ag/Sn–SnO2 Nanosheets Toward CO2 Electroreduction to Pure HCOOH Solutions at Ampere-Level Current - Min Zhang; Aihui Cao; Yucui Xiang; Chaogang Ban; Guang Han; Junjie Ding; Li-Yong Gan; Xiaoyuan Zhou (Nano-Micro Letters)
Highlights The strongly coupled Ag/Sn–SnO2 nanosheets (NSs) were prepared via a versatile electrochemical template strategy, and the generated electron-enriched Sn sites promote the formation of *OCHO and alleviate the energy barriers of *OCHO to *HCOOH. Ag/Sn–SnO2 NSs afford a superior activity toward CO2 electroreduction with current densities up to 2000 mA cm‒2 and near-unity selectivity for formate production. Ag/Sn–SnO2 NSs as the cathode in a membrane electrode assembly with porous solid electrolyte reactor enable the direct production of ~ 0.12 M pure HCOOH solution for 200 h.